Quality and safety of fresh sugarcane juice sold by street vendors: a growing public health concern - Abdelaziz Ed-Dra; Abdulrahman Mohammed Alhudhaibi; Emad M. Abdallah; Luca Nalbone (Frontiers in Sustainable Food Systems, 2025)
Sugarcane juice is a nutrient-rich beverage with numerous health benefits. However, in Morocco, the safety and quality and of fresh sugarcane juice have not been adequately assessed. To bridge this gap, a total of 100 sugarcane juice samples sold by street vendors in the city of Beni Mellal, Morocco, were collected between February and June 2024 and analyzed for key quality and safety parameters, including the evaluation of the microbiological quality and safety of fresh sugarcane juice sold in Morocco, the analysis of its physicochemical properties, and the assessment of the potential health risks linked with its consumption. Physicochemical analysis revealed a pH of 5.23 ± 0.09, total titratable acidity (TTA) of 0.16 ± 0.02% (g citric acid equivalent/100 mL), and total soluble solids (TSS) of 18.48 ± 0.69 °Brix. The juice exhibited notable bioactive properties, with total phenolic content (TPC) of 90.25 ± 8.02 mg GAE/100 mL, total flavonoid content (TFC) of 46.83 ± 8.79 mg QE/100 mL, vitamin C content of 11.25 ± 1.55 mg/100 mL, and DPPH scavenging activity with IC50 of 72.45 ± 7.07 g/L. Microbiological assessment indicated contamination with Total Aerobic Mesophilic Flora, total coliforms, fecal coliforms, yeasts and molds, staphylococci at a level of 5.79 ± 0.36, 3.78 ± 0.33, 1.67 ± 0.34, 3.73 ± 0.23, and 2.81 ± 0.23 log CFU/mL, respectively. Additionally, Escherichia coli was detected in 77% of samples and Staphylococcus aureus was found in 7% of samples, while Salmonella and Listeria monocytogenes were no detected. Antimicrobial susceptibility revealed high resistance of E. coli and S. aureus to ampicillin, penicillin, streptomycin, and tetracycline, with multidrug-resistant (MDR) profiles identified in 40.26% of E. coli and 42.86% of S. aureus isolates. Notably, 24.67% of E. coli and 42.86% of S. aureus isolates exhibited a multiple antibiotic resistance (MAR) index > 0.2, indicating a high-risk contamination source. Moreover, conventional PCR analysis revealed the presence of the sea gene in one S. aureus isolate (14.28%). Additionally, the stx1 and stx2 genes were detected in 8 (10.39%) and 5 (6.49%) E. coli isolates, respectively. In contrast, the hlyA gene was not detected in any of the E. coli isolates. Our results underscore a serious public health concern, emphasizing the urgent need for improved hygienic practices and regulatory monitoring fresh juice sold by street vendors in Morocco.